Efektivitas Mengonsumsi Bubur Kacang Hijau terhadap Peningkatan Produksi Bagi Ibu Menyusui - Anjeli, Mariana; Hasmi, Marselina Y.; Lova, Merlinda E.N.; Murni, Maria T.N.; Setia, Mariyene P.; Sudirman, Maria V.; Alvirah, Marsela J.; Jelita, Modesta; Ndawih, Maria Y.; Avila, Marselina Y.; Trisnawati, Reineldis E. (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
The postpartum period is a period of recovery for the mother after childbirth which is very important to support the success of exclusive breastfeeding, as breast milk is the best source of nutrition that is most important to the baby during the first six months of life. However, many breastfeeding mothers stop breastfeeding early because they feel that milk production is insufficient, which is partly due to a lack of nutrient intake, especially essential proteins and vitamins such as those contained in mung beans. This activity includes the preparation stage (licensing, coordination, and preparation of materials), implementation (pre-test, counseling, demonstration videos, and post-test), and evaluation carried out through discussions with midwives and participants. The pre-test results showed that 25% of respondents had insufficient knowledge, 50% were adequate, and 25% were good. Meanwhile, the post-test results showed a significant increase, with 62.5% of respondents in the category of good knowledge. This indicates that educational interventions through counseling and direct practice are effective in increasing breastfeeding mothers' understanding of the importance of nutrition to support breast milk production. A community-based educational approach that involves hands-on practice and is tailored to the local context has been shown to be effective in increasing breastfeeding mothers' awareness and knowledge of the importance of nutritious intake, particularly mung bean consumption, to support the success of exclusive breastfeeding. Green beans are scientifically proven to contain protein, iron, and vitamin B1 that help stimulate the hormones prolactin and oxytocin, which support breast milk production, so they can be considered natural galactagogo.